Determining the Influence of Technology, Logistic Integration and Operational Performance on Supply Chain with Moderating Role of Information Sharing - Intan Yanuarisma; Lilik Sugiharti (International Journal of Supply Chain Management, 2020)
The basic objective of the ongoing article is to investigate the impact of technology integration, logistic integration and operational performance on the supply chain activities of the services sector in Indonesia. The goals also include the examination of the moderating role of supply chain management information sharing among the links of technology integration, logistic integration, operational performance and supply chain activities of the services sector in Indonesia. The data has been obtained by using the questionnaires from the employees that are associated with the supply chain activities while analysis was made with the help of smart-PLS. The results indicated that technology integration, logistic integration and operational performance have positive linkage with supply chain activities of the services sector in Indonesia. The findings also exposed that supply chain information sharing system has positively moderated among the links of technology integration, and supply chain activities of the services sector in Indonesia. These findings have provided help to the upcoming studies to examine this topic in future along with regulation-making authorities who want to develop the policies for effective supply chain activities that enhance the firm performance.